Implementation of a whole of hospital sepsis clinical pathway in a cancer hospital: impact on sepsis management, outcomes and costs. Issue 3 (6th July 2018) - Thursky, Karin; Lingaratnam, Senthil; Jayarajan, Jasveer; Haeusler, Gabrielle M; Teh, Benjamin; Tew, Michelle; Venn, Georgina; Hiong, Alison; Brown, Christine; Leung, Vivian; Worth, Leon J; Dalziel, Kim; et al.
Abstract : Infection and sepsis are common problems in cancer management affecting up to 45% of patients and are associated with significant morbidity, mortality and healthcare utilisation. Objective: To develop and implement a whole of hospital clinical pathway for the management of sepsis (SP) in a specialised cancer hospital and to measure the impact on patient outcomes and healthcare utilisation. Methods: A multidisciplinary sepsis working party was established. Process mapping of practices for recognition and management of sepsis was undertaken across all clinical areas. A clinical pathway document that supported nurse-initiated sepsis care, prompt antibiotic and fluid resuscitation was implemented. Process and outcome measures for patients with sepsis were collected preimplementation (April–December 2012), postimplementation cohorts (April–December 2013), and from January to December 2014. Results: 323 patients were evaluated (111 preimplementation, 212 postimplementation). More patients with sepsis had lactate measured (75.0% vs 17.2%) and appropriate first dose antibiotic (90.1% vs 76.1%) (all p<0.05). Time to antibiotics was halved (55 vs 110 min, p<0.05). Patients with sepsis had lower rates of intensive care unit admission (17.1% vs 35.5%), postsepsis length of stay (7.5 vs 9.9 days), and sepsis-related mortality (5.0% vs 16.2%) (all p<0.05). Mean total hospital admission costs were lower in the SP cohort, with a significant difference in admission costs between historical and SP non-surgical groups of A8363 (95% CI 81.02 to 16645.32, p=0.048) per patient on the pathway. A second cohort of 449 patients with sepsis from January to December 2014 demonstrated sustained improvement. Conclusions: The SP was associated with significant improvement in patient outcomes and reduced costs. The SP has been sustained since 2013, and has been successfully implemented in another hospital with further implementations underway in Victoria.